2017
DOI: 10.18632/oncotarget.14660
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram to predict lymph node metastasis in patients with early gastric cancer

Abstract: BackgroundLymph node status is crucial to determining treatment for early gastric cancer (EGC). We aim to establish a nomogram to predict the possibility of lymph node metastasis (LNM) in EGC patients.MethodsMedical records of 952 EGC patients with curative resection, from 2002 to 2014, were retrospectively retrieved. Univariate and multivariate analysis were performed to examine risk factors associated with LNM. A nomogram for predicting LNM was established and internally validated.ResultsFive variables signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Lager tumor size, depressed type, and poor differentiation were proved to be independent risk factors in the present study which coincides with previous studies [19][20][21]. Lager tumor size, depressed type, and poor differentiation indicated worse biological behavior, which might also indicate higher probability of LNM.…”
Section: Discussionsupporting
confidence: 92%
“…Lager tumor size, depressed type, and poor differentiation were proved to be independent risk factors in the present study which coincides with previous studies [19][20][21]. Lager tumor size, depressed type, and poor differentiation indicated worse biological behavior, which might also indicate higher probability of LNM.…”
Section: Discussionsupporting
confidence: 92%
“…Among all the high‐risk factors for LNM in EGC, lymphovascular invasion is the most important and has been demonstrated in almost all published studies with the highest OR of LNM, which was also confirmed in this multicenter study. This fact has been used as a contraindication of endoscopic therapy for EGC in both Japanese and Chinese clinical practice guidelines on EGC therapy .…”
Section: Discussionsupporting
confidence: 86%
“…Nomograms have been widely used for quantifying the risk factors of various diseases [ 32 , 33 ]. The effects of several separate variables are integrated by a nomogram to give an individualized risk assessment for each patient.…”
Section: Discussionmentioning
confidence: 99%